Penerapan Metode Six Sigma dalam Analisis Kualitas Produk (Studi Kasus Perusahaan Pemroduksi Baja Tulang Beton) - Afrizal Faturochman; Indro Prakoso; Ayu Anggraeni Sibarani; Katon Muhammad (LPPM ITK, 2020)
The development of the industrial world from the manufacturing sector must always be carried out by each manufacturing company so that the products marketed are not dead in the market because they are less competitive than their competitors. This is what drives companies to always supervise and make improvements to improve the quality of the products produced. PT.XYZ is one of the manufacturing companies engaged in the national steel industry whose main activity is producing concrete reinforcement steel with the main raw material being hot billets. In carrying out its production, PT.XYZ is not uncommon to find the products that are rejected due to defects. This research was conducted to analyze the number of defective goods produced with the aim that the quality of the products obtained increases and the level of income obtained is more leverage using the Six Sigma method. Cause and effect diagrams (fishbone diagrams) and Pareto diagrams are also used in this study to determine the causes of existing problems and the scale of priority problems that must be solved first. Based on the calculation of the percentage of damage, it can be concluded that there are four cases of the highest defect products, namely: 63.93% non-standard length, 15.51% ear defects, 12.67% digestion, and 7.9% cracking. At the end of this study, the results show that the capability and sigma value of company performance in improving product quality amounted to 7916.2 DPMO with a sigma value of 3.916.